2009
DOI: 10.1097/nen.0b013e3181922348
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1 Reduction Parallels the Accumulation of Tau in Alzheimer Disease

Abstract: Aging and metabolism-related disorders are risk factors for Alzheimer disease (AD). Since sirtuins may increase the lifespan through regulation of cellular metabolism, we compared the concentration of sirtuin 1 (SIRT1) in the brains of AD patients (n = 19) and controls (n = 22) using Western immunoblots and in situ hybridization. We report a significant reduction of SIRT1 (mRNA: −29%; protein: −45%) in the parietal cortex of AD patients, but not in the cerebellum. Further analyses in a second cohort of 36 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
277
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(303 citation statements)
references
References 65 publications
12
277
0
Order By: Relevance
“…Global cognition scores obtained before death would suggest that the decrease in SIRT1 levels is related to the accumulation of amyloid-b and t in the cerebral cortex of persons with AD [119]. On the other hand, it was also reported that in age-related cataracts in healthy older humans there was a lower level of SIRT1 expression, and the levels of SIRT1, p53, FOXO3, and FOXO4 were comparable to data from young subjects [120].…”
Section: Sirtuins and Mammalian Agingsupporting
confidence: 48%
See 1 more Smart Citation
“…Global cognition scores obtained before death would suggest that the decrease in SIRT1 levels is related to the accumulation of amyloid-b and t in the cerebral cortex of persons with AD [119]. On the other hand, it was also reported that in age-related cataracts in healthy older humans there was a lower level of SIRT1 expression, and the levels of SIRT1, p53, FOXO3, and FOXO4 were comparable to data from young subjects [120].…”
Section: Sirtuins and Mammalian Agingsupporting
confidence: 48%
“…Analysis of specimens from human brain regions of healthy and Alzheimer disease (AD) subjects showed that SIRT1 expression at both the RNA and the protein level is significantly decreased in the parietal cortex of AD patients, whereas cortical expression was not affected [119]. Global cognition scores obtained before death would suggest that the decrease in SIRT1 levels is related to the accumulation of amyloid-b and t in the cerebral cortex of persons with AD [119].…”
Section: Sirtuins and Mammalian Agingmentioning
confidence: 99%
“…38 A large body of evidence suggests a central role of mitochondrial dysfunction associated with oxidative stress as culprits in the pathophysiology of chronic neurodegenerative disorders such as Alzheimer's disease (AD), Parkinson's disease (PD) or Huntington's disease (HD), 39 in which SIRT1 may play a primary role. 1 Thereby, a decrease in SIRT1 expression has been detected in AD, 40 PD 41 and HD 42 patient brain samples, which is correlated with decreased PGC-1α activity. [43][44][45] Indeed, the promotion of SIRT1 activity either genetically or pharmacologically with RSV, has been shown to combat several pathological hallmarks of neurodegeneration in a variety of models for AD, [46][47][48][49] and HD, 51,52 supporting the neuroprotective notion of SIRT1 activation.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, SIRT1 activation reduced amyloid pathology in a mouse model of AD, and crossing SIRT1 knockout mice with these mice dramatically increased the Aβ burden (Donmez et al 2010). Moreover, decreased SIRT1 expression has been found in patients with AD, and this decrease correlates with tau and Aβ levels (Julien et al 2009). Modulation of ADAM10 expression by SIRT1 has also been demonstrated (Gutierrez-Cuesta et al 2008;Donmez et al 2010).…”
Section: Discussionmentioning
confidence: 99%